Alcohol drinking, ADH1B and ADH1C genotypes and the risk of postmenopausal breast cancer by hormone receptor status: the Netherlands Cohort Study on diet and cancer. (20th July 2018) - Hahn, Markus; Simons, Colinda C J M; Weijenberg, Matty P; van den Brandt, Piet A
Abstract: Alcohol consumption has consistently been shown to increase breast cancer (BC) risk. This association may be modified by single nucleotide polymorphisms (SNPs) in alcohol dehydrogenase (ADH) isoenzymes ADH1B and ADH1C . The Netherlands Cohort Study comprises 62 573 women, aged 55–69 years at baseline (1986). Follow-up for postmenopausal BC for 20.3 years was available. Genotyping of six tag SNPs in ADH1B and ADH1C was performed on DNA from toenails. A case−cohort approach was used for analysis (complete data available for n subcohort = 1301; n cases = 1630). Cox regression models for postmenopausal BC were applied to determine marginal effects of alcohol intake and SNPs using a dominant genetic model, as well as multiplicative interaction of the two. Results were also obtained for subtypes by estrogen receptor (ER) and progesterone receptor (PR) status. Multiple testing was adjusted for by applying the false discovery rate (FDR). Alcohol intake (categorical) increased the risk of postmenopausal BC ( P trend = 0.031). Trends for ER and PR subgroups followed a similar pattern. Continuous modeling of alcohol resulted in a hazard rate ratio (HR) for overall postmenopausal BC of 1.09 (95% confidence interval: 1.01–1.19) per 10 g/day of alcohol. SNPs were not associated with BC risk. No effect modification of the alcohol−BC association by SNP genotype was seen after FDR correction in overall BC and ER/PR subgroups. In conclusion, alcohol consumption was shown to increase the risk of postmenopausal BC. This association was not significantly modified by common SNPs in ADH1B and ADH1C, neither in overall BC nor in hormone receptor-defined subtypes. Abstract : Drinking alcohol is associated with increased BC risk. Common SNPs in ADH1B and ADH1C might modify this association. In the Netherlands Cohort Study, no such modification is seen, neither in overall disease nor in hormone receptor subtypes.